2009
DOI: 10.1159/000211716
|View full text |Cite
|
Sign up to set email alerts
|

Area at Risk and Viability after Myocardial Ischemia and Reperfusion Can Be Determined by Contrast-Enhanced Cardiac Magnetic Resonance Imaging

Abstract: Background/Aims: Clinical differentiation between infarcted and viable myocardium in the ischemic area at risk is controversial. We investigated the potential of contrast-enhanced cardiac magnetic resonance imaging (ceCMRI) in determining the area at risk 24 h after ischemia. Methods: Myocardial ischemia was induced by percutaneous coronary intervention of the left anterior descending coronary artery in pigs. Coronary occlusion time was 30 min in group A, which caused little myocardial infarction and 45 min in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Recently, Vosseler et al [46] demonstrated in an animal model the feasibility to determine the area at risk and myocardial viability early after myocardial ischemia-reperfusion using LGE. Furthermore, automatic quantifi cation approaches based on thresholds have been tested, as a way to increase reproducibility and to facilitate multicenter comparisons but they are not fully validated.…”
Section: Assessment Of Myocardial Viabilitymentioning
confidence: 99%
“…Recently, Vosseler et al [46] demonstrated in an animal model the feasibility to determine the area at risk and myocardial viability early after myocardial ischemia-reperfusion using LGE. Furthermore, automatic quantifi cation approaches based on thresholds have been tested, as a way to increase reproducibility and to facilitate multicenter comparisons but they are not fully validated.…”
Section: Assessment Of Myocardial Viabilitymentioning
confidence: 99%